Potencies and Threats of The Demographic Bonus on The Quality of Human Resources and Economy in Indonesia 2019 - Febby Risandini; Rini Silvi (Politeknik Statistika STIS, 2021)
The success of Indonesia’s development is marked by increasing economic growth, which is in line with the demographic transition, where the number of people who are borne is less than the population which bears it. Indonesia will enter the peak of the demographic bonus in 2030, where every 100 productive aged people bear 46 to 47 non-productive-aged people. The demographic bonus can positively impact on the economy and the quality of human resources if its potential is adequately utilized but becomes a threat if not maximized. Therefore, path analysis is used in this study to analyze the potencies and threats of the demographic bonus and its effect on economic growth, either directly or indirectly through the quality of human resources. The results of this study are the potential index consisting of labor absorption, household savings, and women in the labor market does not significantly influence on the quality of human resources and economic growth. Meanwhile, the threats index, which consists of internet access, migration, and child marriage, has a significant positive direct effect on economic growth and a significant negative indirect effect on economic growth. These results indicate that the threat index has a greater influence than the potential and it is hoped that the government will focus on reducing the threat of the demographic bonus, but it must be accompanied by an increase in the quality of human resources.